There's a simpler formula for convergent series if the first term is 1. You have to identify a single number to multiply each successive term by which requires you to chop Q up as you have done.Call this multiplier "M".Sum = 1 / (1-M)S = 1 / (1-1/4)S = 1 / (3/4)S = 1.33Works for the meta-summing of Q too.
Note: Only a member of this blog may post a comment.
There's a simpler formula for convergent series if the first term is 1. You have to identify a single number to multiply each successive term by which requires you to chop Q up as you have done.
ReplyDeleteCall this multiplier "M".
Sum = 1 / (1-M)
S = 1 / (1-1/4)
S = 1 / (3/4)
S = 1.33
Works for the meta-summing of Q too.